(3cTa GdeZjH aj GdMSGH HGdQHY GdeLjHs - (3Ydj Hf EHQGgje Hf eMeO GdCfUGQj GdehbJ, CHh GdMSf YdGA GdOjf, GdeYQha HGHf GdTGWQ,J (B777 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3bO CcKQhG cPG GdeJbOejf hGdeJCNQjf ef GdcdGe ai cd Yde eG NdG fhY GdMSGH HGdQHY GdeLjH jYfi HGdVQH hGdbeSg hGdLPQ heG jJaQZ ef Pdc s
(3BNQgG (B:s
(3hGdeGd eQHYgG hgh SJg hKdGKhf hghjYOd NeSg CLRGQg hSJg OQGge aGYde Pdc hbS Ydjg s
(3jNJda Chdg h BNQg Yf QSGdI GHf GdTGWQ GdeSeGI GdeZjH ai GdQHGY GdeLjHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B251 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B8s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B126 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B88 s
Keywords: (3Gdadcs